IMPLEMENTATION OF RESOURCE BASED VIEW MODEL IN BUILDING COMPETITIVENESS IN ISLAMIC BOARDING SCHOOL - Chotimah, Chusnul; Effendi, Muchammad Irfan; Sulistyorini, Sulistyorini; Ahmad, Ahmad; Miftahuddin, Miftahuddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Nowadays, competition in the world of education is unavoidable. Educational institutions are also motivated to provide their best service to the community for the institution's sustainability. Educational institutions must work hard to excel in the competition so that new formulations, strategies and innovations are needed. One of the right strategies to choose and implement is the Resourcebased view (RBV) strategic management model. This research aims to look deeper into how Islamic Boarding Schools maximize their resources so they can be competitive with other educational institutions. The case study research method was chosen by researchers with a qualitative approach with school principals, teachers, students and guardians of students. The results of the study show that strategic management of the Resource-based view (RBV) model at the Islamic Boarding School Ar Robithoh can build competitiveness by maximizing human resources as human capital and maximizing structural capital and relational capital because these aspects are valuable, exclusive, difficult to imitate, and cannot be replaced.